(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
VacZineNations! is a collaborative artwork led by Rachelle Viader Knowles and Mkrtich Tonoyan, produced by artists, students, and designers in the UK, Canada, China, and Armenia, and exhibited as part of <Immune Nations> at Galleri KiT in Trondheim, Norway, and UNAIDS in Geneva, Switzerland, in 2017. This critical dialogue text gives insight into the necessarily messy approach used to develop a project with over one hundred participants, working from multiple disciplinary and geographic perspectives. This text is accompanied by a second essay that positions the artwork within the context of practice-led research (see Knowles, “VacZineNations! as Practice-Led Research” in this volume).